Functional Restoration of the Superior Auriculocephalic Sulcus in Cryptotia: A Case Report Validating the Twin Compression Theory via an Extended Sub-Galeal Advancement Flap - Stevani Irwan; Al Hafiz (HM Publisher, 2026)
Background: Cryptotia, characterized by the invagination of the superior helix beneath the temporal skin, presents significant functional challenges regarding the retention of eyewear and protective masks. While prevalent in East Asian populations, data from the Indonesian archipelago is scarce. This study aims to document the functional and aesthetic outcomes of a modified surgical technique in a monozygotic twin, addressing the twin compression etiological hypothesis. Case presentation: A 7-year-old male monozygotic twin presented with Type I Cryptotia of the right ear, with a superior helix-to-mastoid distance of 0 mm. The co-twin exhibited normal auricular morphology. The patient underwent a partial otoplasty combined with a modified posterior auricular advancement flap. The specific modification involved extended sub-galeal undermining to recruit maximum tissue elasticity. Cartilage reshaping was performed using non-absorbable horizontal mattress sutures. Postoperative evaluation at 3 months revealed a superior helix-mastoid distance increase to 12 mm and an auriculocephalic angle restoration to 30 degrees. Patient-Reported Outcome Measures via a validated Visual Analog Scale showed an improvement from 2 to 9 out of 10. No immediate recurrence or hypertrophic scarring was observed. Conclusion: The extended sub-galeal advancement flap offers a promising solution for sulcus restoration, prioritizing vascularity and tissue recruitment over skin grafting. This case supports the intrauterine mechanical compression theory as a viable etiology for sporadic cryptotia. Short-term results are robust, though long-term surveillance is required to monitor cartilage memory.